Percentage difference of resistivity of nanoparticles in determining crude oil using sand-pack experimental method - Mohd Zulkifli, Mohamad Noor; Mariyamni, Awang; Sonny, Irawan (The Malaysian Analytical Sciences Society, 2017)

(untitled)
Nanoparticle with its nanoscale can be used as a data collector in every part of the development of the petroleum field. By having a hydrophilic condition for the nanoparticles, it can move to the targeted area in the water zone. The hydrophilic condition will differentiate between oil zone and water zone. The objective of the study is to use the hydrophilic nanoparticles to detect the oil and water zones using sand-pack displacement test. An experiment using the sand-pack method was done to show that the hydrophilic nanoparticles can be used to collect data. The nanoparticles used were aluminum oxide (Al) and nickel zinc ferrite oxide (NiZnFeO). The results showed that for NiZnFeO, at 3-inch distance from the injection point, the percentage difference increased from 15% to 25%, while for Al2O, the nanoparticles also showed the same increment but different in values, which were from 6% to 15%. This is shown by the significant change of resistivity percentage at the 3-inch distance. To conclude, the use of both types of nanoparticles that have hydrophilic nanoparticles can show the significant changes for resistivity at internal short front face of well reservoir with oil zone only.